Can legislation mandating vaccination solve the challenges of routine childhood immunisation in Nigeria?. (2nd January 2016) - Onyemelukwe, Cheluchi
ABSTRACT: In Nigeria, childhood mortality is very high, with almost a million children dying each year. A fifth of these die from vaccine-preventable diseases. The role of immunisation in preventing childhood morbidity and mortality is widely recognised. Unfortunately little, if any, account has been given of the law's role in immunisation in legal discourse in Nigeria. Yet recent steps have been taken at both federal and state levels to compel immunisation using the instrument of legislation. For instance, the Child Rights Act, a domestication of the Convention of the Rights of the Child, passed in 2003 includes provisions compelling immunisation. Also, several states in Nigeria like Jigawa, Niger and Katsina States, have recently enacted legislation that makes childhood immunisation compulsory under the law. These pieces of legislation criminalise refusal to immunise children and also public statements that discourage immunisation. I identify the challenges that limit or obstruct uptake of immunisation in Nigeria and ask what role the law can play in providing solutions to these challenges. I examine the ways in which the law has been engaged to promote immunisation, the impact of law and the limits of legislative intervention. I also suggest ways to improve the law's effectiveness in this essential public health matter.